Analysis of the changes and difficulties arising from kidney transplantation: a qualitative study - Daniela Cristina Sampaio de Brito; Alessandra Moregola de Paula; Fabiane Rossi dos Santos Grincenkov; Giancarlo Lucchetti; Hélady Sanders-Pinheiro (Universidade de São Paulo, 2015)
OBJECTIVE: to identify the main gains and stressors perceived by the patient, one year subsequent to kidney transplantation.METHOD: a qualitative study, in which the data were obtained and analyzed through the Discourse of the Collective Subject and frequency counting, with the participation of 50 patients who had received kidney transplantation.RESULTS: the sample presented a mean age of 44±12.8 years old, and a predominance of males (62%). The principal positive changes provided by the transplant were: return to activities; freedom/independence; well-being and health; strengthening of the I; and closening of interpersonal relationships. The most-cited stressors were: fear; medication; excess of care/control; specific characteristics of the treatment; and failure to return to the social roles.CONCLUSION: kidney transplantation caused various positive changes in the patient's routine, with the return to activities of daily living being the most important gain, in the participants' opinion. In relation to the stressors, fear related to loss of the graft, and questions relating to the immunosuppressive medication were the main challenges to be faced following transplantation.